Figurações do indígena na ficção rio-grandense - Deuschle, Agnes Hübscher (2008)
The figure of the Indian has been a theme in many works and has been approached in multifaceted ways in Brazilian literature. The variegated focus given to the figure of the Indian in literature requires careful analysis. The Indians' Figurations in Rio-Grandense Fiction undertakes to investigate, in the context of the relationships between history and literature, the construction of the Indian in Rio-Grandense fiction. The hypothesis considers that, as it has been observed in the socio-historical reality, the Indian, in literature, is customarily silenced by the dominant culture. The basis for analysis includes Guarani characters Pedro Missioneiro (O Continente I, VERISSIMO, 1949) and Francisco Abiaru (Breviário das terras do Brasil, ASSIS BRASIL, 1988). The choice of this corpus is the consequence of thematic proximity and several narrative and intertextual similarities regarding the Guarani historical context. For the study of the figure of the Indian in literature, we considered the conceptual notions of the construction and representation of the reality in fictional discourse, as drawn from Erich Auerbach's essay Figura (1939), and from his book Mímesis (1946).